Representation of the Frame HEALTHY/UNHEALTHY EATING in American Media Discourse - E. R. Kulchitskaya (Дискурс, 2023)
Introduction. The  article  considers  the  problem  of  frame  modeling  of  the  HEALTHY/ UNHEALTHY EATING concept applying the methods of corpus linguistics. The scientific novelty of the study is determined by the fact that no previous attempts have been made to model the  frame  of  the  HEALTHY/UNHEALTHY  EATING  concept.  The  relevance  of  the  research  is conditioned by the use of the collocation method to study the structure of the frame.Methodology  and  sources.  The  analysis  of the  structure  of  the  HEALTHY/UNHEALTHY EATING concept was based on the method of frame modeling and the method of collocation allocation.  The  collocations  selected  in  the  texts  of  the  News  on  the  Web  (NOW)  corpus served as an empirical basis for the study. The NOW corpus contains more than 16 billion words of data from web newspapers and magazines.Results  and  discussions.  The  article  presents  a  hierarchical  model  of  the HEALTHY/UNHEALTHY  EATING  frame,  highlights  the  following  terminal  slots “healthy/unhealthy  food(s)”,  “healthy/unhealthy  cooking”,  “healthy/unhealthy  weight”, “eating  regularity”,  “eating  moderation”,  “eating  balance”,  “eating  mindfulness”,  “eating irregularity”,  “eating  excessiveness”,  “eating  imbalance”,  “eating  mindlessness”,  “eating disorders”. The analysis of the collocations obtained, verbalizing each separate slot of the HEALTHY/UNHEALTHY  EATING  frame  in  the  NOW  case,  allowed  us  to  draw  conclusions about the structure of subordinate subframes.Conclusion. The study shows that each individual slot of the frame under consideration has a complex structure, including terminal nodes-slots. The analysis of the selected collocations reveals  those  aspects  of  the  HEALTHY/UNHEALTHY  EATING  concept  that  are  most  often discussed  in  media  discourse.  This  includes  ideas  about  eating  mindfulness,  regularity, moderation, eating disorders and various types of diets.